Magnitude of unintended pregnancy and its determinants among childbearing age women in low and middle-income countries: evidence from 61 low and middle income countries - Aragaw, Fantu Mamo; Amare, Tsegaw; Teklu, Rediet Eristu; Tegegne, Biresaw Ayen; Alem, Adugnaw Zeleke (Frontiers in Reproductive Health, 2023)
Background: Unintended pregnancy is one of the most serious health issues in low and Middle-Income Countries (LMICs), posing significant health, economic, and psychosocial costs to individuals and communities. However, there is limited evidence on the prevalence of unintended pregnancies and their determinants in LMICs. Hence, this study aimed to assess the prevalence of unintended pregnancy and its associated factors among childbearing-age women in LMICs. Method: Data for the study were drawn from a recent 61 Demographic and Health Surveys (DHS) conducted in LMICs. A total sample of 187,347 mothers who gave birth in the five years preceding the survey was included. STATA version 16 was used to clean and analyze the data. Multilevel multivariable logistic regression was employed to identify individual and community-level factors of unintended pregnancy in LMICs. In the multivariable analysis, an adjusted odds ratio with a 95% confidence level was reported to indicate statistical association. Results: The pooled magnitude of unintended pregnancy in LMICs was 26.46%%( 95% CI: 25.30%, 27.62%), ranging from 19.25%% in Egypt to 61.71% in Bolivia. Working status [AOR= 1.03; 95% CI; 1.01, 1.06], having a husband with primary education [AOR= 1.05; 95% CI; 1.01, 1.11], women from the richest household[AOR=0.95; 95% CI; [0.91,0.99], media exposure [AOR=1.05; 95% CI; 1.02, 1.08], residence [AOR=1.04; 95%CI; 1.01, 1.07], distance from a health facility [AOR=1.04; 95%CI; 1.01, 1.06] were significantly associated with unintended pregnancy. Conclusion: Unintended pregnancy rates remain high in LMICs. Women whose husband has a primary education, women with media exposure, working status, women who live in an urban area, and women with a big problem of distance to health facilities were variables that were significant predictors of unintended pregnancy. When attempting to minimize unintended pregnancy in LMICs, these factors need to be considered. Furthermore, most of these attempts should be driven by government entities in low and middle-income countries.